Single video games improve cognitive functioning in college students: evidence from behavioral and fNIRS assessments - Li, Chuangtao; Guo, Xiaodan; Wang, Jingsong; Wang, Shen (Frontiers in Psychiatry, 2025)
ObjectiveIn the digital intelligence era, video games have become highly popular among college students, with the duration of playtime escalating rapidly. There is a growing research interest in video games to improve cognitive function, and video games have shown great potential in improving cognitive function. However, most of the current studies have focused on the effects of long-term gaming experience or short-period gaming training on cognitive functioning, and it remains unknown whether a single session of video gaming is equally effective. The primary aim of this study was to evaluate the impact of a single gaming session on the cognitive functions of college students and to explore its underlying mechanisms.MethodsForty-three college students from a university in Fuzhou City were recruited and randomly assigned to either the VG group (video game) or the nVG group (non-video game). Pre- and post-test behavioral and functional near-infrared spectroscopy (fNIRS) data were collected from the participants. The statistics were analyzed using repeated measures ANOVA, with simple effects analysis conducted if interaction effects were significant, and corrections applied using the Bonferroni method.Results(1) Following the video game session, the VG group exhibited shorter RT (reaction times), higher ACC (accuracy), and greater RCS (response correctness scores), whereas the nVG group experienced longer RT, lower ACC, and lower RCS. (2) In the VG group, post-test concentrations of Oxy-Hb in channels 6, 9, and 29 were elevated, particularly in the bilateral orbitofrontal cortex (OFC) and left dorsolateral prefrontal cortex (DLPFC), while there was minimal change in prefrontal cortex (PFC) activation levels in the nVG group.ConclusionsCognitively engaging video games can effectively enhance the cognitive abilities of male college students. The underlying mechanism may be closely related to the promotion of prefrontal lobe activation by video games, which in turn improves reflective ability, processing speed, and decision-making levels.